Health promotion and schools: how to move forward - Daniela Gardano Bucharles Mont'Alverne; Ana Maria Fontenele Catrib (Universidade de Fortaleza, 2014)
The health promotion action means, described by the 1986 Ottawa Charter, highlights the creation of supportive environments for health(1). Following this line of reasoning, several strategies have been adopted for implementing health promotion policies, including the Health Promoting School. In 1995, the Pan American Health Organization / Regional Office for the Americas of the World Health Organization (PAHO/WHO) officially launched the Regional Health Promoting School Initiative. Since then, all the countries in Latin America and the Caribbean have strengthened school health promotion actions, rethinking school health activities(2). To become a Health Promoting School, the institution must take a comprehensive view of human beings - especially children and adolescents - in their familiar, community and social environment. It must provide a healthy environment, building constructive and harmonious relationships and hence being able to awaken skills and attitudes within participants, fostering autonomy, creativity and participation of students and also the whole school community(3). Never before has so much been said about health and health promotion as today, i.e., there is a need for promoting health at school as an element for changing reality. The school plays an important political role within this context for being a place where ideology can be constructed, destroyed or perpetuated through the transmission of values and beliefs, besides being an environment that favors the development of health education actions. Childhood is the defining moment for the construction and solidification of habits and attitudes, hence the importance of school as an environment that enhances the development of a targeted, systematized and permanent work. "Through the Health Promoting School Initiative, school health has a chance to move forward and expand its conception and practices with a comprehensive and interdisciplinary view of the human being within a broader community, environmental and political context"(4:6). The Health Promoting School seeks to develop knowledge, skills and dexterity for self care and prevention of risk behaviors. In addition, it creates education strategies to awaken - through a critical and reflexive analysis - values, behaviors, social conditions and lifestyles, and contributes to the improvement of health and human development, helping to construct citizenship and democracy, strengthening solidarity, community spirit and human rights(3). According to the Pan American Health Organization, health promotion at school has three main components: general health education, creation of a healthsupportive environment and provision of healthcare services(4). If we are to promote health, we can rely on school as a partner in this journey; and if we are to develop health education actions at school, we must rely on teachers' support and commitment. The teacher's role at school is complex and deserves attention because he is a (trans)formative agent(3,4). The realization of health promotion projects at school is supported by the teacher who represents an important and fundamental link, being a multiplier of ideas who should, therefore, be trained to approach the concept of health recommended in the International Conferences, the VIII National Healthcare Conference, Healthcare Public Policies and the National Curriculum Parameters (PCN) (1), not only through the handling of information but also educational strategies needed for an integrated construction of knowledge. This current issue of the Brazilian Journal in Health Promotion (Revista Brasileira em Promoção da Saúde - RBPS) features an article on the importance of the creation of a healthy environment at school, especially when it occurs in a region with low socioeconomic status. The article shows that the creation of a healthy environment since preschool years - besides being important - has an impact on children's lives. Simple actions such as recreational activities at school, provided they are continuous, reflect on a remarkable learning. The RBPS believes that promoting the qualification of teachers and healthcare professionals, through its pages, will serve as a cornerstone of the Health Promoting School in Brazil and an example for other countries to share this idea. doi:10.5020/18061230.2013.p307